Determinants of the processes of selecting and orienting football players towards playing positions in Algerian football clubs - Arab, Abderrahim; Mohamedi, Mehdi (Journal of Human Sciences, 2022)
The aim of our study is to know the determinants of the processes of selection and orientation of soccer players to playing positions, and for this we used the descriptive approach based on a questionnaire applied to a sample of 30 coaches U15 and U17 of the Regional League of Batna who were selected by random method, and we found that the majority of coaches do not rely on physical and physiological tests and morphological measurements to select and orient players to playing positions, but they are satisfied only with a pedagogical observation through games of selection and orientations, and based on the results of the study, the research group recommended the need to develop a standardized test battery that youth trainers rely on for selection and orientation processes.